Model Simulasi Smarthome Berbasis Internet of Things dan Cloud Computing Menggunakan Cisco Packet Tracer - Tariq Aziz; tengku moh diansyah; Risko Liza (Unit Pengelola Jurnal Universitas Harapan Medan, 2022)
The development of technology at this time is very high where what we can see and take advantage of is growingrapidly along with the times to meet human needs. One of them is the increasing need for safe and comfortablehome technology. The application of technology in the house can be found in the smarthome concept.Smarthome is a home concept that uses a variety of IoT devices available for use at home to make it smart. Suchdevices include motion detectors, lawn sprinklers, smart doors, and many other IoT devices. Nowadays,simulation has become important in many ways, especially in various studies and studies carried out using thesimulation method as a way to solve problems. Cisco Packet Tracer 7.3 is an application that can help insimulating IoT devices. The results obtained from the smarthome simulation are the concept of house doorsecurity, air conditioning control and automatic fire extinguishing which can run well but the heating elementfor the increase in room temperature is slow.